Impact Force Identification by Using Modal Transformation Method in Collocated and Non-Collocated Cases - Abdul Ghaffar, Abdul Rahman; Khoo, Shin Yee; Zubaidah, Ismail; Chong, Wen Tong; Noroozi, Siamak (Faculty Mechanical Engineering, UMP, 2013)
Considering the impact location is inaccessible, impact force determination by using remote responses away from the impact location must be developed. A methodology utilizing operating deflection shape (ODS) analysis, modal analysis (MA) and modal transformation method (MTM) to evaluate the dynamic force is presented. A four ground supported lightweight plate is used as the test rig in this study. The performance of this approach in collocated and non-collocated cases is demonstrated via experiment. By measuring the response and frequency response function (FRF) of the test rig, the time history of unknown force is recovered by the proposed method where impact location is known in a priori. This force determination method is examined at two discrete impact locations. It shows that the collocated case had a better accuracy of force determination result compared to non-collocated case. Furthermore, result shows that both cases can have acceptable force determination result if the curve fitting result is good